Global supply chains in Chinese industrialization: Impact on waste scavenging in developing countries - Martin Medina (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
China has undergone remarkable economic growth spearheaded by industrialization. Chinese industry demands a wide variety of raw materials in increasing amounts in order to manufacture all kinds of products. Industrial demand exceeds domestic supply for several materials. Thus, China needs to import raw materials. In order to satisfy its needs, China has developed global supply chains, which link two apparently separate worlds: its industry and millions of scavengers that recover recyclable materials from waste in developing countries. This paper examines this new phenomenon and argues that it has been mostly beneficial to the poor in developing countries.
Keywords: L11; L13; 330; China; industrialization; recycling; scavenging